A Mini‐Twister Variant and Impact of Residues/Cations on the Phosphodiester Cleavage of this Ribozyme Class. Issue 50 (16th October 2015) - Košutić, Marija; Neuner, Sandro; Ren, Aiming; Flür, Sara; Wunderlich, Christoph; Mairhofer, Elisabeth; Vušurović, Nikola; Seikowski, Jan; Breuker, Kathrin; Höbartner, Claudia; Patel, Dinshaw J.; Kreutz, Christoph; et al.
Abstract: Nucleolytic ribozymes catalyze site‐specific cleavage of their phosphodiester backbones. A minimal version of the twister ribozyme is reported that lacks the phylogenetically conserved stem P1 while retaining wild‐type activity. Atomic mutagenesis revealed that nitrogen atoms N1 and N3 of the adenine‐6 at the cleavage site are indispensable for cleavage. By NMR spectroscopy, a p K a value of 5.1 was determined for a 13 C2‐labeled adenine at this position in the twister ribozyme, which is significantly shifted compared to the p K a of the same adenine in the substrate alone. This finding pinpoints at a potential role for adenine‐6 in the catalytic mechanism besides the previously identified invariant guanine‐48 and a Mg 2+ ion, both of which are directly coordinated to the non‐bridging oxygen atoms of the scissile phosphate; for the latter, additional evidence stems from the observation that Mn 2+ or Cd 2+ accelerated cleavage of phosphorothioate substrates. The relevance of this metal ion binding site is further emphasized by a new 2.6 Å X‐ray structure of a 2′‐OCH3 ‐U5 modified twister ribozyme. Abstract : Efficient cleavage of the twister ribozyme class does not require the phylogenetically conserved stem P1. The shifted p K a of the adenine at the cleavage site together with Mn 2+ ‐ or Cd 2+ ‐accelerated cleavage of S P phosphorothioate substrates suggest the combination of nucleobase‐assisted acid–base catalysis and metal‐ion catalysis.